2020
DOI: 10.3390/molecules25153437
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VCAM-1 and Anti-IL4Rα Aptamer-Conjugated Super Paramagnetic Iron Oxide Nanoparticles for Enhanced Breast Cancer Diagnosis and Therapy

Abstract: The surface protein overexpressed on cancer cells can be used as biomarkers for early detection of specific diseases. Anti-VCAM-1 and anti-IL4Rα DNA aptamers specific to VCAM-1 and IL4Rα receptors that are overexpressed in 4T1 tumor-bearing mice could be used as potential biomarker for both diagnostic and therapeutic applications in cancer biology. Cell Viability and luciferase assay of 4T1-Luc2 cancer cells in the presence of anti-VCAM-1 ssDNA or anti-IL4Rα RNA aptamers was assessed by monitoring the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Already discussed anti-VCAM-1 aptamer conjugated SPIONs, apart from demonstrating favorable tumor imaging ability, were also investigated for tumor growth suppression ( 131 ). When injected along with anti-IL-4Rα aptamer-conjugated SPIONs to tumor bearing mice, these two NMs significantly decreased tumor size comparing to control or single NM-treated animals, indicating that simultaneous functional blockade of these targets potentiates antitumor activity.…”
Section: Nanomedicines Targeting Camsmentioning
confidence: 99%
“…Already discussed anti-VCAM-1 aptamer conjugated SPIONs, apart from demonstrating favorable tumor imaging ability, were also investigated for tumor growth suppression ( 131 ). When injected along with anti-IL-4Rα aptamer-conjugated SPIONs to tumor bearing mice, these two NMs significantly decreased tumor size comparing to control or single NM-treated animals, indicating that simultaneous functional blockade of these targets potentiates antitumor activity.…”
Section: Nanomedicines Targeting Camsmentioning
confidence: 99%
“…Anti-VCAM-1 and anti-IL4Rα DNA aptamers, specific for their cognate receptors overexpressed in 4T1 mammary tumor-bearing mice, were shown by Chinnappan et al 9 to be useful for diagnosis and therapy when conjugated to super paramagnetic iron oxide nanoparticles (SPIONs). Receptor binding by both aptamers triggers tumor cell apoptosis, thus limiting tumor progression in vitro and in vivo.…”
Section: Breast Cancermentioning
confidence: 99%
“…Like the use of SPIONs for breast cancer, 9 these magnetic NPs were studied by Fang et al 19 using the known prostate cancer (PC)-specific aptamer, Wy5a, for delivery of Docetaxel (Dtxl), a broad-spectrum anticancer drug. These targeted SPIONs showed controlled drug-release in PC-3 cells in vitro and in vivo, as well as MRI contrastenhancement, plus more efficacious antitumor properties in vivo without systemic toxicity.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Many studies have also been conducted on the phosphate adsorption capabilities of IONPs for the removal of phosphate contaminants from wastewater systems; however, it should be noted that these studies typically used bare IONPs, where the surfaces are passivated only with hydroxyl groups. Nevertheless, these studies demonstrate a clear affinity of phosphate ions for the IONP surface. Despite these key findings, the use of PB and PBS for IONP preparations and applications prevails to this day. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Tris is another commonly used biological buffer for IONP applications (Table ), ,,, despite previous studies, which have demonstrated the ability of the hydroxyl arms of Tris to chelate Fe­(III), as well as the possibility of the amine to participate in complex formation in solution. , Furthermore, a study by Sosa-Acosta et al used Tris as a capping ligand on IONPs and proposed that binding occurs through the hydroxyl groups, leaving the amines free for coupling chemistry. The Tris, however, was added during the co-precipitation synthesis of the IONPs, as opposed to a postsynthesis ligand exchange, so its ability to displace existing ligands was not investigated.…”
Section: Introductionmentioning
confidence: 99%